Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
To prove the given statement using mathematical induction, we follow two main steps: the base case and the inductive step.
Base Case: We start by verifying the statement for ( n = 1 ): [ \sum_{k=1}^{1} k^3 = 1^3 = 1 ] [ \frac{12(1+1)2}{4} = \frac{1 \cdot 2^2}{4} = 1 ] Since both sides equal 1, the base case holds true.
Inductive Step: Assume the statement is true for some integer ( n ), which is our inductive hypothesis: [ \sum_{k=1}^{n} k^3 = \frac{n2(n+1)2}{4} ]
Now we need to prove the statement for ( n + 1 ): [ \sum_{k=1}^{n+1} k^3 = \sum_{k=1}^{n} k^3 + (n+1)^3 ] Using the inductive hypothesis, we replace the sum up to ( n ): [ \frac{n2(n+1)2}{4} + (n+1)^3 ]
Simplify and factor to show that it equals to ( \frac{(n+1)2(n+2)2}{4} ), thus completing the inductive step.
Conclude that, by the principle of mathematical induction, the statement is true for all integers ( n \geq 1 ).
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.